(untitled) (INNOVATIVE ECONOMY, 2025)
Tkachenko A.M., Chernova I.V. HISTORICAL EVOLUTION OF MANAGEMENT CONCEPTS: FROM THE DOMINANCE OF AUTHORITARIAN MODELS TO THE MODERN STRATEGIC APPROACH Purpose. The aim of the article is to comprehensively cover the historical evolution of management theories with an emphasis on the transition from the dominance of authoritarian models to modern strategic approaches, as well as the identification the key factors that contributed to this transformation. Methodology of research. It is based on the comprehensive application of historical and logical, systemic, and comparative methods, which allows for a thorough reconstruction of the chronology and content of the evolution of management theory. The historical and logical method is used to analyse the evolution of management thought and identify patterns in its development. Comparative analysis allowed us to compare classical and modern management models according to key characteristics. The systemic approach was used to consider management concepts as integral entities formed under the influence of economic, social, and technological factors. The method of content analysis of scientific publications ensured the generalization of the current scientific discourse and the identification of leading trends in the development of management theory. The method of analogy and extrapolation was used to substantiate possible directions for the further transformation of management concepts. Findings. The article provides a comprehensive theoretical and methodological analysis of the historical evolution of management concepts in the context of the transformation of social and economic systems. It substantiates the transition from the dominance of authoritarian, hierarchically oriented management models to modern strategic and adaptive approaches based on the integration of behavioural, systemic, and resource concepts. A comparison of authoritarian models with modern strategic approaches is presented from the perspective of efficiency, adaptability, consideration of the human factor, and organizational culture. It is proven that modern management models do not deny the achievements of classical schools, but instead synthesize their rational elements with modern concepts of leadership, teamwork, and strategic analysis. Originality. Theoretical and methodological approaches to analysing the historical evolution of management concepts based on a systematic combination of classical authoritarian models and modern strategic approaches have been further developed. It has been substantiated that the effectiveness of modern management systems is determined not by the complete rejection of authoritarian models, but by the integration of their structured elements (formalization, hierarchy, standardization) into adaptive and behaviour-oriented management concepts. The conceptual approach to the use of historical management models as a basis for the formation of modern strategic paradigms capable of functioning in conditions of digital transformation and high turbulence of the external environment has been improved. Practical value. The results of the study can be used to develop strategies for managing organizations in conditions of instability, digital transformation, and the growing role of behavioural and social factors. Key words: history of management, management theory, strategic management, authoritarian models, managerial thought, management evolution, behavioural concepts, management paradigms.